2008
DOI: 10.1097/mcg.0b013e3180f6262c
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the DNA Repair Gene XPA and XPC and its Correlation With Gastric Cardiac Adenocarcinoma in a High Incidence Population in North China

Abstract: XPA A23G and XPC exon 8 Val499Ala polymorphisms may be useful markers for identifying individuals at risk of developing GCA in the high incidence region of north China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
2
31
2
Order By: Relevance
“…As studies with the same population by different investigators or overlapping data by the same authors were found, the most recent or complete articles with the largest numbers of subjects were included. 14,17,36 All eligible studies were examined carefully, and their bibliographies were checked for other relevant publications.…”
Section: Identification and Eligibility Of Relevant Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As studies with the same population by different investigators or overlapping data by the same authors were found, the most recent or complete articles with the largest numbers of subjects were included. 14,17,36 All eligible studies were examined carefully, and their bibliographies were checked for other relevant publications.…”
Section: Identification and Eligibility Of Relevant Studiesmentioning
confidence: 99%
“…5 To date, a number of molecular epidemiological studies have been done to evaluate the association between XPA À4G>A polymorphism and different types of cancer risk in diverse populations. The tumor types included lung cancer, 6,13,22,24,[29][30][31][32][33][34] gastric cancer, 7,17 colorectal cancer, 8,12,23 squamous cell carcinoma of the head and neck, 8,10 basal and squamous cell carcinomas of the skin (BCC and SCC), 20,27 breast cancer, 8,18,26 esophageal cancer, 11,14,15 and so on. However, the results were inconsistent or even contradictory.…”
mentioning
confidence: 99%
“…Certain single nucleotide polymorphisms in the XP gene have been seen with a higher frequency in sporadic gastric carcinomas and have been proposed to be useful markers for identifying high-risk individuals [148].…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…colorectal adenoma [33] ); (6) only the one with a larger sample size was selected if the case-control study was included by more than one articles using the same case serious; and (7) if the case-control study covered more than one cancer type using the same control subjects, we never separate them as several independent studies but combined the cancers of the same category together and consider them as one. In the current study, data for meta-analysis were available from 14 articles, including 4,562 cancer cases and 6,593 controls for Lys939Gln (11 studies from 11 articles) [19][20][21][22][23][24][25][26][27][28][29] , 2,496 cases and 3,653 controls for Ala499Val (6 studies from 6 articles) [19,23,24,26,27,29] , 1,429 cases and 2,724 controls for PAT+/-(7 studies from 7 articles) [19,22,26,27,[30][31][32] , respectively.…”
Section: Identification and Eligibility Of Relevant Studiesmentioning
confidence: 99%
“…The reason why researchers neglected digestive system neoplasm might be due to the limited study numbers relevant to this topic (less than five in the above mentioned metaanalyses). [19][20][21][22][23][24][25][26][27][28][29][30][31][32] . To estimate the overall relationship of the three polymorphisms on digestive system cancer risk, as well as to quantify the potential between-study heterogeneity, a meta-analysis including 14 the most recently published and relevant articles was performed in present study.…”
Section: Introductionmentioning
confidence: 99%